Technical methods for forming post-modern arts and their manifestations in the products of students of Art Education (pop art as an example) (Al-Academy, 2025)
The research dealt with the topic of technical methods for forming post-modern arts and their manifestations in the products of art education students, which occur in displaying and directing their artistic achievement. The research contained four chapters. The first chapter dealt with: the methodological framework of the research, represented by the research problem, which was manifested in the following questions:1- What are the technical methods used to form postmodernism, including pop art, which art education students adopted in their completed artistic productions, and in which they demonstrated their artistic treatments that were embodied in the composition and directing of the completed artistic work.2- What transformations occurred in the students’ productions through their use of materials and raw materials using modern and contemporary techniques and methods to communicate the idea and topic through the style of popular art (pop art). The goal of the research: (Discovering the technical methods for forming post-modernism (pop art) and its manifestations in the products of art education students) The researcher identified the limits of the research, which were represented by the products of the students of the Art Education Department / College of Fine Arts / University of Baghdad for the academic year (2022- 2023), and then moved to the second semester. Which included two sections, the title of the first section was (technical methods of postmodern arts), while the second section discussed (technical methods (pop art) The researcher extracted a number of indicators that resulted from the theoretical framework, while the third chapter dealt with the research methodology and procedures. The fourth chapter included the research results, conclusions, recommendations and proposals. The research came out with a set of results, the most important of which are: 1. Using different technical methods in the structure of shapes by following the technique of assembling and installing different materials such as cloth, photographs, newspaper pieces, wood material, ropes, inks, and different dyes.The various technical methods contributed to activating the forms of artistic work and the diversity of display spaces, through multiple techniques such as collage, rubbing, notching, dotting, pouring, rubbing, and high dough.Among the most important conclusions are:1. Different technical methods contributed to activating the forms of artistic work and the diversity of display spaces, through multiple techniques such as collage, rubbing, notching, dotting, pouring, rubbing, and high dough